SISTEM KEPERCAYAAN MASYARAKAT DI DAERAH ALIRAN SUNGAI (DAS) UNDA KABUPATEN KLUNGKUNG - Ida Bagus Astika Pidada; I Nyoman Djuana; Ni Made Suwendri (Universitas Warmadewa, 2018)
[Title: The System of Community Trust in the Unda Watershed Klungkung Regency] The Unda River watershed (DAS) is located in Klungkung Regency. The Unda watershed is derived from 7 rivers: (1) Bajing River, (2) Barak River, (3) Krekuk River, (4) Mangening River, (5) Masin River, (6) Sah River, and (7) Telagawaja River. The length of the river is 24,400 meters, 77 meters wide, 80 to 1 meter deep, 75 meters in height with 5.422 liter / second up to 7,390 liter / sec of water flow. The upper limit of the Unda River is Telagawaja River, including the Selat Village, Klungkung District, while the downstream of this river ends in Banjar Karangdadi and Banjar Pasurungan, Kusamba Village, Dawan Subdistrict, which further extends into the sea to the Badung Strait. The river is almost never dry throughout the year. Communities in this river still have a system of trust for cultural activities, one of the cultural elements of the religious system that is still used this river for the bath (pesiraman) the gods (betara). In addition, people still use this river for self-cleaning, sacrificial sacrifice, ashes, and fertility and safety ceremonies. This place is still trusted by the community as a sacred place because it is inhabited by such subtle creatures: memedi, tonya, wang samar / gamang.